2018
DOI: 10.1021/acsami.8b08636
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylenimine-Modified Membranes for CO2 Capture and in Situ Hydrogenation

Abstract: Enzymatic CO reduction can provide value-added chemicals from greenhouse gases at ambient temperature and pressure. However, poor solubility of CO results in a low conversion rate. In this work, polyethylenimine (PEI) was attached onto the surface of poly(acrylic acid)-grafted (PAA-grafted) polyethylene membranes, and then, the membranes were used in an integrated process of CO capture and in situ hydrogenation. Modification conditions were optimized with a surface amino group density of PEI-modified membranes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…According to Wang et al, the reaction rate of enzymatic conversion of CO 2 was increased from 0.280 to 6.90 μM by grafting PEI on the support for capture CO 2 . 44 Also, Jiang et al reported that methanol concentration was increased by increasing local CO 2 concentration, which was ascribed to the switching of the equilibrium to the product side. 45 PDA/PEI contributed therefore to improve methanol concentration by increasing local CO 2 concentration.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Wang et al, the reaction rate of enzymatic conversion of CO 2 was increased from 0.280 to 6.90 μM by grafting PEI on the support for capture CO 2 . 44 Also, Jiang et al reported that methanol concentration was increased by increasing local CO 2 concentration, which was ascribed to the switching of the equilibrium to the product side. 45 PDA/PEI contributed therefore to improve methanol concentration by increasing local CO 2 concentration.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Furthermore, local CO 2 concentration around enzymes was enhanced by PDA/PEI coating, owing to a large amount of amino groups on PDA/PEI that could capture CO 2 . According to Wang et al., the reaction rate of enzymatic conversion of CO 2 was increased from 0.280 to 6.90 μM by grafting PEI on the support for capture CO 2 . Also, Jiang et al reported that methanol concentration was increased by increasing local CO 2 concentration, which was ascribed to the switching of the equilibrium to the product side .…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, polyethyleneimine (PEI) with high affinity to CO 2 was introduced to the surface of the carboxyl-functionalized polymer membrane that was then applied in an integrated process of CO 2 capture and in situ enzymatic hydrogenation, and the initial reaction rate was increased by 24.6 times, much higher than all reported. This finding proves that the PEI-modified material may be a promising candidate for process intensification of the enzymatic conversion of CO 2 .…”
Section: Introductionmentioning
confidence: 94%
“…Unless specified otherwise, all enzymatic reactions were carried out at 37 °C and 170 rpm in 0.05 M PB (pH 6.0), and in a sealed stainless-steel reactor. 24 Typically, PDA/ PEI-SiO 2 was added to the reaction solution (2 mL) containing 50 mM NADH and 2 mg of FDH. After being purged with CO 2 , the reactor was sealed and kept at 0.5 MPa.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…At present, a series of solid adsorbents mainly include zeolite, activated carbon, hydrotalcite, metal oxides, and solid amine adsorbents [8][9][10][11][12]. Amino-modified adsorbents have high selective adsorption capacity (they adsorb CO 2 in the air instead of N 2 ) and higher CO 2 adsorption capacity [13,14]. Meanwhile, amine-modified adsorbents can be divided into impregnation and grafting methods according to their different synthesis methods.…”
Section: Introductionmentioning
confidence: 99%